Armed Conflict and Early Human Capital Accumulation: Evidence from Cameroon's Anglophone Conflict - Hector Galindo-Silva; Guy Tchuente (Global Labor Organization (GLO), 2023)
This paper examines the impact of the Anglophone Conflict in Cameroon on human capital accumulation. Using high-quality individual-level data on test scores and information on conflict-related violent events, a difference-in-differences design is employed to estimate the conflict's causal effects. The results show that an increase in violent events and conflict-related deaths causes a significant decline in test scores in reading and mathematics. The conflict also leads to higher rates of teacher absenteeism and reduced access to electricity in schools. These findings highlight the adverse consequences of conflict-related violence on human capital accumulation, particularly within the Anglophone subsystem. The study emphasizes the disproportionate burden faced by Anglophone pupils due to language-rooted tensions and segregated educational systems.
Keywords: I25; O15; D74; J24; 330; Anglophone Conflict; Cameroon; human capital accumulation; educational outcomes; language-based conflicts